2011
DOI: 10.4306/pi.2011.8.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Emotional Eating and Visuospatial Deficits Whereas Shared Risk Factors Related with Social Support between Anorexia Nervosa and Bulimia Nervosa

Abstract: ObjectiveAlthough it is thought that eating disorders result from the interplay of personal and sociocultural factors, a comprehensive model of eating disorders remains to be established. The aim of this study was to determine the extent to which the childhood factors and deficit in visuoperceptual ability contribute to eating disorders.MethodsA total of 76 participants - 22 women with anorexia nervosa (AN), 28 women with bulimia nervosa (BN), and 26 healthy women of comparable age, IQ, and years of education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
7
25
0
Order By: Relevance
“…Studies measuring the accuracy of copy have shown either equivalent (Castro-Fornieles et al, 2009; Danner et al, 2012; Lopez et al, 2008; Sherman et al, 2006; Stedal et al, 2012) or poorer performance in AN relative to control groups (Kim, Lim, & Treasure, 2011; Lopez, Tchanturia, Stahl, & Treasure, 2009). One study found that underweight participants with AN performed worse than controls on copy, but improved after gaining 10% of body weight (Kingston, Szmukler, Andrewes, Tress, & Desmond, 1996), suggesting that the deficit may be weight-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies measuring the accuracy of copy have shown either equivalent (Castro-Fornieles et al, 2009; Danner et al, 2012; Lopez et al, 2008; Sherman et al, 2006; Stedal et al, 2012) or poorer performance in AN relative to control groups (Kim, Lim, & Treasure, 2011; Lopez, Tchanturia, Stahl, & Treasure, 2009). One study found that underweight participants with AN performed worse than controls on copy, but improved after gaining 10% of body weight (Kingston, Szmukler, Andrewes, Tress, & Desmond, 1996), suggesting that the deficit may be weight-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…One study found that underweight participants with AN performed worse than controls on copy, but improved after gaining 10% of body weight (Kingston, Szmukler, Andrewes, Tress, & Desmond, 1996), suggesting that the deficit may be weight-dependent. The majority of studies, which included adolescents and children along with adults, found significantly worse delayed recall in AN (Andres-Perpina et al, 2011; Camacho, 2008; Favaro et al, 2012; Lopez et al, 2008; 2009; Mathias & Kent, 1998; Pendleton-Jones, 1991; Sherman et al, 2006; Stedal et al, 2012; Tenconi et al, 2010; Thompson, 1993), or a trend for worse delayed recall (Castro-Fornieles et al, 2009), but some found equivalent performance (Danner et al, 2012; Kim, 2011; Kingston et al, 1996; Murphy, Nutzinger, Paul, & Leplow, 2002). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several risk factors for developing an eating disorder characterized by extreme restrictive eating (e.g., AN) have been identified. These include: (1) psychological risk factors , such as depression, low self-esteem, weight and shape concerns, and body dissatisfaction [14,15]; (2) familial risk factors , such as family discord, parental dieting, and parental encouragement to diet [16,17]; (3) and social risk factors , such as deficient social support, general or weight-specific peer teasing, and peer dieting [1719]. While existing studies have expanded the field's understanding of risk factors, they are limited by narrowly focusing on development of a particular disorder (e.g., AN) and over-utilization of clinic-based samples.…”
Section: Which Factors Predict Escalation Of Restrictive Eating Durinmentioning
confidence: 99%
“…Broadly, research indicates that interpersonal distrust predicts the onset, but not maintenance of EDs [60••]. Further, deficient social support may contribute to both AN and BN [89].…”
Section: Sociocultural Factors Implicated In Ed Riskmentioning
confidence: 99%